A 5′ fragment of Xist can sequester RNA produced from adjacent genes on chromatin. Issue 13 (22nd May 2019) - Lee, David M; Trotman, Jackson B; Cherney, Rachel E; Inoue, Kaoru; Schertzer, Megan D; Bischoff, Steven R; Cowley, Dale O; Calabrese, J Mauro
Abstract: Xist requires Repeat-A, a protein-binding module in its first two kilobases (2kb), to repress transcription. We report that when expressed as a standalone transcript in mouse embryonic stem cells (ESCs), the first 2kb of Xist ( Xist -2kb) does not induce transcriptional silencing. Instead, Xist -2kb sequesters RNA produced from adjacent genes on chromatin. Sequestration does not spread beyond adjacent genes, requires the same sequence elements in Repeat-A that full-length Xist requires to repress transcription and can be induced by lncRNAs with similar sequence composition to Xist -2kb. We did not detect sequestration by full-length Xist, but we did detect it by mutant forms of Xist with attenuated transcriptional silencing capability. Xist -2kb associated with SPEN, a Repeat-A binding protein required for Xist -induced transcriptional silencing, but SPEN was not necessary for sequestration. Thus, when expressed in mouse ESCs, a 5′ fragment of Xist that contains Repeat-A sequesters RNA from adjacent genes on chromatin and associates with the silencing factor SPEN, but it does not induce transcriptional silencing. Instead, Xist -induced transcriptional silencing requires synergy between Repeat-A and additional sequence elements in Xist . We propose that sequestration is mechanistically related to the Repeat-A dependent stabilization and tethering of Xist near actively transcribed regions of chromatin.